PHARMACOGNOSTIC INVESTIGATION ON ELAEOCARPUS BLASCOI WEIBEL LEAVES - A. VIJAYAN; C. SEBASTIAN RAJASEKARAN (International Journal of Pharma and Bio Sciences, 2010)
Cissus quadrangularis Linn. is a succulent plant of family Vitaceae commonly found in tropical and subtropical xeric wood. It is a fleshy, cactus-like liana widely used as a common food item in India. The plant contains calcium oxalate, β-carotene, ascorbic acid, β-sitosterol and 3-ketosteroids, also falvonoids such as quercetin, and kaempferol. The stem contains two unsymmetric tetracyclic tri terpenoids, onocer-7-ene-3α, 21β-diol and onocer- 7-ene-3β, 21 α –diol, two steroidal principles I and II, δ-amyrin, δ-amyrone. The plant is prescribed in the ancient Ayurvedic literature as a general tonic and analgesic, with specific bone fracture healing properties. In the present studies pharmacognostic investigation done on basis of macroscopy, microscopy and physicochemical parameters. These findings will be useful towards establishing quality control parameter for the standardization of the drug.